2014
DOI: 10.1371/journal.pone.0100466
|View full text |Cite
|
Sign up to set email alerts
|

Insulin-Mimicking Bioactivities of Acylated Inositol Glycans in Several Mouse Models of Diabetes with or without Obesity

Abstract: Insulin-mimetic species of low molecular weight are speculated to mediate some intracellular insulin actions. These inositol glycans, which are generated upon insulin stimulation from glycosylphosphatidylinositols, might control the activity of a multitude of insulin effector enzymes. Acylated inositol glycans (AIGs) are generated by cleavage of protein-free GPI precursors through the action of GPI-specific phospholipase C (GPI-PLC) and D (GPI-PLD). We synthesized AIGs (IG-1, IG-2, IG-13, IG-14, and IG-15) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 53 publications
0
8
0
Order By: Relevance
“…In contrast, GPI-PLD may be cleaved when inositol groups are acylated, supposedly releasing acylated IPGs (A-IPGs) ( Figure 1 C) [ 92 ]. Synthetic A-IPGs also show a strong insulin-mimetic activity [ 93 ]. Non-protein linked GPIs are intermediate GPIs, as they quickly bind proteins when reaching the plasma membrane surface.…”
Section: Insulin-mimetic and Insulin-sensitizing Properties Of Inomentioning
confidence: 99%
“…In contrast, GPI-PLD may be cleaved when inositol groups are acylated, supposedly releasing acylated IPGs (A-IPGs) ( Figure 1 C) [ 92 ]. Synthetic A-IPGs also show a strong insulin-mimetic activity [ 93 ]. Non-protein linked GPIs are intermediate GPIs, as they quickly bind proteins when reaching the plasma membrane surface.…”
Section: Insulin-mimetic and Insulin-sensitizing Properties Of Inomentioning
confidence: 99%
“…Comparable studies in humans are lacking and the potential role of GPLD1 in diabetes and prediabetes is currently unknown. GPLD1 cleavage generates second messengers that can act as insulin-mimetic low molecular mass species [33,34]. Suzuki et al demonstrated that treatment of mice with certain insulin-mimetic low molecular mass species led to decreased plasma glucose levels, increased glycogen content in the liver and skeletal muscles, and improved glucose tolerance in db/db mice and C57B6N mice on high-fat diets [34].…”
Section: Discussionmentioning
confidence: 99%
“…Synthetic GPIs and IPGs and the relationship between structure and function Since the isolation and structural elucidation of natural IPGs has been difficult, chemists have produced a range of synthetic GPIs, IPGs and inositol glycans in order to better understand structure-function relationships and identify possible drug candidates (Larner, Brautigan, and Thorner 2010;Goel and Azev 2009;Suzuki et al 2014). While many of these candidates showed insulin mimetic activity in various assays, the strength of the effect, and whether the effect was on glucose, glycogen or lipid metabolism varied by molecular structure (Larner, Brautigan, and Thorner 2010;Goel and Azev 2009;Suzuki et al 2014). These effects were reviewed by Goel et.al.…”
Section: P-ipgs and A-ipgsmentioning
confidence: 99%